CARBONATE RESERVOIR CHARACTERIZATION USING SIMULTANEOUS SEISMIC INVERSION IN THE MENTAWA-MINAHAKI FORMATION, âGASâ FIELD, BANGGAI BASIN, CENTRAL SULAWESI - Achmad Insani Rahadian, Kem
The Banggai Basin is one of the productive oil and gas basins in Indonesia. The Mentawa - Minahaki Formation as a carbonate reservoir has complex characteristics where its porosity has high heterogeneity due to the diagenesis process, especially in the carbonate reef build-up of the Mentawa Formation which has been proven as a gas reservoir. To evaluate the carbonate rock reservoir, reservoir characterization was carried out for further optimization of the development of the Mentawa - Minahaki Formation carbonate rock "GAS" field in the Senoro - Toili Block. In this study, 3D Gather seismic data, Velocity RMS, and two well data were used. Reservoir characterization analysis was carried out using the simultaneous inversion method. This method is carried out using partial angle stack seismic data to analyze the effect of the wave incidence angle, so that simultaneous seismic inversion can utilize information on differences in amplitude response based on angle. Sensitivity analysis shows that density and lambda-rho parameters are sensitive to identify gas fluids in carbonate rocks, and acoustic impedance can be used to identify porous, less porous, and tight carbonates and have a linear trend to porosity, so that the results of acoustic impedance inversion can be used to predict porosity values. Furthermore, the results of carbonate facies identification show that the research field has characteristics consisting of two types, namely the upper part in the form of reefal facies and the lower part in the form of platform carbonate facies. The results of simultaneous inversion can map the distribution of carbonate reservoir zones containing hydrocarbons, indicated by P-Impendance values (<8500 m/s*g/cc), density (<2.15 g/cc) and low lambda-rho (<24 GPa), and high porosity values up to (>26%) in the carbonate reef build-up area. High porosity in reef build up shows the influence of relative sea level changes, in accordance with the vadose zone diagenesis event that occurred in the Banggai Basin which has contributed to increasing the porosity of carbonate rocks.